Genome-wide CRISPR/Cas9 screen reveals JunB downmodulation of HIV co-receptor CXCR4 - Schulze, William J.; Gregory, Devon A.; Johnson, Marc C.; Lange, Margaret J. (Frontiers in Microbiology, 2024)
HIV-1 relies extensively on host cell machinery for replication. Identification and characterization of these host-virus interactions is vital to our understanding of viral replication and the consequences of infection in cells. Several prior screens have identified host factors important for HIV replication but with limited replication of findings, likely due to differences in experimental design and conditions. Thus, unidentified factors likely exist. To identify novel host factors required for HIV-1 infection, we performed a genome-wide CRISPR/Cas9 screen using HIV-induced cell death as a partitioning method. We created a gene knockout library in TZM-GFP reporter cells using GeCKOv2, which targets 19,050 genes, and infected the library with a lethal dose of HIV-1NL4-3. We hypothesized that cells with a knockout of a gene critical for HIV infection would survive while cells with a knockout of a non-consequential gene would undergo HIV-induced death and be lost from the population. Surviving cells were analyzed by high throughput sequencing of the integrated CRISPR/Cas9 cassette to identify the gene knockout. Of the gene targets, an overwhelming majority of the surviving cells harbored the guide sequence for the AP-1 transcription factor family protein, JunB. Upon the generation of a clonal JunB knockout cell line, we found that HIV-1NL4-3 infection was blocked in the absence of JunB. The phenotype resulted from downregulation of CXCR4, as infection levels were recovered by reintroduction of CXCR4 in JunB KO cells. Thus, JunB downmodulates CXCR4 expression in TZM-GFP cells, reducing CXCR4-tropic HIV infection.